A Multilingual Turn: Translanguaging by Design Activity in an EFL Context - Kufakunesu Zano (Universitas Pendidikan Mandalika, 2022)
Translanguaging can be the latest all-embracing approach in language policy and assessment needed to substitute previous linguistic practices that treated languages as separate entities in a globalised world. This study is based on translanguaging by analysing activities that involved two cartoons in a multilingual classroom. This research was conducted to determine the opinions of Grade 12 EFAL learners on translanguaging by design activity in a multilingual setting. Grade 12 EFAL were chosen for their rich exposure to analysing cartoons. The class had 35 learners who were put in 5 focus groups to analyse the two cartoons. The 2017 cartoon had 5 questions and the 2018 cartoon had 4 questions, which learners answered in groups. The results indicate that translanguaging is an empowering tool that gives the learners a sense of ownership and belonging as they manipulate their previous linguistic knowledge to explore the given task. The teacher needs to alert the learners that they are free to use their home languages together with English to do an activity. This will help learners realise that there is not much difference between English and their home languages as they answer the questions. Teachers need to be multilingual so that they remain culturally and linguistically relevant to the learners.